Teaching and learning for library and information studies during the Covid-19 lockdown at the University of Limpopo, South Africa - Seema, Tumelo Jacob (My University, 2023)
The World Health Organization declared Covid-19 as a pandemic that posed a contemporary threat to humanity. This pandemic forced a global shutdown of several activities, including educational activities, and this resulted in tremendous crisis-response migration of universities with online learning serving as the educational platform. Many venue-based institutions such as the University of Limpopo approved the shift of their traditional pedagogical approach to entirely online teaching and learning. The aim of this study was to investigate teaching and learning for Library and Information Studies during the Covid-19 lockdown at the University of Limpopo, South Africa. The study adopted quantitative approach and a self-administered questionnaire was the main instrument used to collect data from fourth-level students registered for a Bachelor of Information Studies at University of Limpopo. Forty-one questionnaires were returned, and the study used descriptive analysis to analyse quantitative data. The study found that library and information studies (LIS) students had a negative perception towards online teaching and learning. The study also found that a lack of technical skills, loadshedding and an unconducive learning environment are major challenges for students to accept online teaching and learning. Furthermore, the study established that the university management does not provide adequate support for students to cope with online teaching and learning. Based on these findings, the study recommended training for students to have the required technical skills to use for online learning. The study further recommended that online classes should always be recorded for students who missed online classes due to loadshedding to catch up. The university management should confirm that all students are in an environment that is conducive to online learning.
Thesis (M. INF.) -- University of Limpopo, 2023
Keywords: Online learning; Library and Information studies; Covid-19, Lockdown; University of Limpopo; South Africa; Covid-19; Lockdown; Student-centered learning; Computer-assisted instruction; Web-based instruction